Producción de Semillas de Especies Arbóreas en la Pluviselva Valdiviana - Múrua, R.; González, L. A. (Bosque (Valdivia), 1985)
Seed production of trees species in a coastal temperate rain forest in the San Martin Experimental Woods, 74 km from Valdivia, was monthly estimated from 1980 to 1983. Wooden boxes in the forest floor were used to make monthly seed collections covering a total area of 9.375 m 2 . Seeds were weighed and burned in an adiabatic calorimeter Parr bomb in order to obtain the caloric values. Seed production was expressed as biomass (kg/ha) and productivity (kcal/ha). And alternation of years of high (1981 1983) an low crops (1980-1982) was found. The seed production of Aextoxicon punctatum and Gevuina avellana determine this alternancy because these species show, a two years rythm in seed production. Nothofagus obliqua, Podocarpus salignus, Laurelia sempervirens and Laurelia philippiana showed peaks in seed production every three years. Other studied species (Drimys winteri, Eucryphia cordifolia, Myrceugenella apiculata and Lomatia dentata) showed a low production with no evident multiannual rythms. Also a seasonal fluctuation was observer in the mayority of the trees species. Higher seed production is concentrated in summer and autum.